Unraveling mechanisms of mesenchymal stromal cell–mediated immunomodulation through patient monitoring and product characterization. Issue 1 (29th December 2015) - Schepers, Koen; Fibbe, Willem E.
Abstract : Mesenchymal stromal cells (MSCs) are increasingly used in the treatment of a variety of clinical conditions and to modulate immune responses in conditions related to auto‐/alloimmunity, including graft‐versus‐host disease (GvHD). Although pilot data are promising, treatment responses have been highly variable, and further development of this as a therapeutic modality depends on increased insight into the properties of clinical MSC products and on understanding the mechanisms underlying responses in patients. Here we review the mechanisms that possibly underlie the capacity of MSCs to treat auto‐/alloimmunity, and describe how patient monitoring can help to identify the in vivo mechanisms of action in the treatment of GvHD. Since MSCs used in the clinic originate from various donors and from a heterogeneous population of cells, we will also discuss recent insights into MSC heterogeneity and their implications for clinical MSC products. Finally, we describe a framework to improve our understanding of the efficacy and working mechanism of MSCs, which involves patient monitoring and more extensive characterization of the heterogeneity within and between different MSC preparations.